ANALISIS KINERJA PRODUKSI DAN NILAI TAMBAH AGROINDUSTRI KERIPIK SINGKONG DI KELURAHAN GANJAR ASRI KECAMATAN METRO BARAT KOTA METRO - Tika Ariska; Dwi Haryono; Lina Marlina (Lampung University, 2022)
This study aims to analyze the production performance and added value of cassava chips agroindustry in Ganjar Asri Village, West Metro District of Metro City. Respondents of this study are the owners of agro-industry cassava chips. Data were collected from March to April 2021. The analytical methods used are quantitative and qualitative descriptive analysis and Hayami’s Value-Added Analysis. The results show that the procurement of raw materials with six components, namely the time and place of both agroindustries is not correct, while the components of price, type, quality, and quantity are right. The production performance of both agroindustries, on indicators of productivity, production capacity, quality, delivery speed, and process speed are appropriate, and flexibility indicators can not be said to be good because the flexibility of both agroindustries has not been optimal. Agroindustry cassava chips provide an added value greater than zero NT > 0 or positive, so both agroindustries are worth to be developed. The marketing channels carried out by both cassava chip agroindustries are producers - retailers – consumers. Keywords: added value, agroindustry, cassava, marketing.